Using sedatives–hypnotics or opioids in older adults: a narrow path. (24th July 2018) - Davies, Simon J. C.; Mulsant, Benoit H.
Abstract : This issue of International Psychogeriatrics contains three papers from three continents that explore the use of sedatives–hypnotics and opioids in the treatment of older adults (Hamina et al ., 2018 ; Machado-Duque et al., 2018 ; Tseng et al., 2018 ), and a fourth paper reporting on a qualitative study that addresses the broader question of training needs in dementia in a setting of rapid economic and demographic changes (Xu et al ., 2018 ).